Fungsi Pedagang Kaki Lima Dalam Memanfaatkan Tenaga Kerja Keluarga di Jalan Hr. Soebrantas, Kecamatan Binawidya, Kota Pekanbaru - Sanjaya, Andre (Jurnal Ilmiah Wahana Pendidikan, 2024)
Street vendors are one of the dominant informal sectors in urban areas, as a form of scale economic activity that produces and/or distributes goods and services, goods sold on roadsides and city centers that are busy with visitors. In this case, street vendors function in managing family workers. The formulation of the research problem is how street vendors function in creating job opportunities for family workers and the factors he faced. This research is categorized as descriptive research with a qualitative approach, data collection techniques of observation, interviews and research documentation. The results of this research state that the presence of street vendors not only has negative impacts such as destroying the city structure, disturbing road users, causing traffic jams but also has positive sides. Apart from trading to meet their own needs, it can also open up employment opportunities for family workers. With the factors he faces in terms of external limitation such as bad weather, income factor and internal is not fulfilling personal desires, mixing two different problems, limited business capital.